Advances in the molecular regulation of endothelial BMP9 signalling complexes and implications for cardiovascular disease. (24th May 2019) - Wood, Jennifer H.; Guo, Jingxu; Morrell, Nicholas W.; Li, Wei
Abstract : Bone morphogenetic protein 9 (BMP9), a member of the transforming growth factor β (TGFβ) superfamily, is a circulating vascular quiescence and endothelial protective factor, accounting for the majority of BMP activities in plasma. BMP9 and BMP10 bind preferentially to the high-affinity type I receptor activin receptor-like kinase 1 on vascular endothelial cells. Recently, many reports have highlighted the important roles of BMP9 in cardiovascular disease, particularly pulmonary arterial hypertension. In vivo, BMP9 activity and specificity are determined by tightly regulated protein–protein recognition with cognate receptors and a co-receptor, and may also be influenced by other proteins present on the endothelial cell surface (such as low-affinity receptors) and in circulation (such as TGFβ family ligands competing for the same receptors). In this review, we summarise recent findings on the role and therapeutic potential of BMP9 in cardiovascular disease and review the current understanding of how the extracellular protein–protein interaction milieu could play a role in regulating endothelial BMP9 signalling specificity and activity.